Influencia de las deficientes relaciones intrafamiliares en la comunicación de los usuarios del programa de atención integral de salud a personas adultas mayores del Hospital Regional Docente de Trujillo en el año 2017. - Collao Ventura, Fiorella Alexandra (2018)
The present thesis was carried out with the purpose of determining the deficient intrafamilial relationships that influence the communication of the users of the Integral Health Care Program to the Elderly of the Teaching Regional Hospital of Trujillo in the year 2017. The type of research is descriptive, the sample considered was 77 users belonging to the Comprehensive Health Care Program for Older Adults, aged 60 years and over, so the methodology applied is deductive and analytical, where Through the technique of interview, observation, and survey, it was possible to obtain testimonies, events, situations that are presented in the context of users, and also the collection of this research was through the instruments of interview registration, observation record and the questionnaire, in addition to the bibliographic references that served to support the research. With this research that contains theoretical bases that provide the sustenance of the thesis and above all that contributes an important contribution in our society directed to a vulnerable population, it is thus that we try to answer the hypotheses, where the deficient intrafamilial relations frame an aspect important in the communication of older adults, compared to the participation and teamwork that is being done in the program to which they belong. It is concluded that poor intrafamilial relationships significantly influence the communication of the Comprehensive Health Care Program to the Elderly, since having inadequate family support means that the user does not feel motivated to attend the activities of the program , without recognition and praise when a successful activity, having an environment of sub groups and not doing teamwork, which is reflected in the poor dialogue between peers and showing little participation in the development of leisure activities, recreational and educational.